Perspektif konsumen terhadap ritel mix di Primarasa Ahmad Yani surabaya - Fransisca, Happy (Jurnal Strategi Pemasaran, 2014)
This research aims to analyze the Perspectives of consumers against Retail Mix (customer service, store design & display, communication mix, location, merchandise assortment and pricing) Ayam Bakar Primarasa Ahmad Yani Surabaya. This research was carried out by disseminating a questionnaire to 120 consumer respondents Ayam Bakar Primarasa Ahmad Yani Surabaya. Analysis tools are used to measure is a descriptive analysis.The results of this study indicate that the retail element of the indicators applied to Ayam Bakar Primarasa Ahmad Yani Surabaya have been good, but not a maximum.